Purification and characterization of a peptide essential for formation of streptolysin S by Streptococcus pyogenes. - Akao, T (1992)
Peptides in a pronase digest of bovine serum albumin were required for streptolysin S formation by Streptococcus pyogenes besides maltose and a carrier (the oligonucleotide fraction obtained by treatment of Saccharomyces cerevisiae RNA with RNase A). A peptide essential for streptolysin S formation was purified to homogeneity from a pronase digest of bovine serum albumin by Sephadex G-25 column chromatography, and anion-exchange, reverse-phase, and gel filtration high-performance liquid chromatography. The purified peptide was divided into more than two peptides by HCOOOH oxidation and was composed of four residues of cysteine, three of leucine, and one each of aspartic acid and glutamic acid. Leucine and cysteine were detected as amino-terminal residues, and leucine and glutamic acid were detected as carboxyl-terminal residues, suggesting that two or three peptides are linked by a disulfide bond(s). A disulfide bond structure in the peptide seemed to be required for streptolysin S formation.